Conducting polymer based hybrid nano-composites for enhanced corrosion protective coatings - Patil, R. C.; Radhakrishnan, S. (Progress in Organic Coatings, 2006)
Hybrid composite coatings containing zinc oxide (ZnO) and polyaniline (PANI) as nano-additives dispersions were prepared with poly(vinyl acetate) (PVAc) as the major matrix. The steel plates dip-coated with these formulations were tested for corrosion protection by immersion in saline water over long periods. The Tafel plots for the determination of open circuit potential (OCP) and corrosion current (I-corr) were recorded. The coatings containing both ZnO and PANI showed improved corrosion resistance as compared to the single component coating. The I-corr values of PVAc-ZnO-PANI are found to be two-order magnitude lower than that of PVAc and PVAc-ZnO coatings. The results are explained on the basis of enhancement in barrier properties due to nano-particulate additives in PVAc-ZnO-PANI film together with the redox behaviour of PANI and protective oxide layer formation near the substrate. (C) 2006 Elsevier B.V All rights reserved.
Keywords: Coatings; corrosion; nano-additives; polyaniline; ZnO